2021
DOI: 10.1111/aji.13438
|View full text |Cite
|
Sign up to set email alerts
|

Potential biomarkers of infertility associated with microbiome imbalances

Abstract: Problem The aim of this study was to investigate the possible relationship between vaginal/rectal microbiome disbalances and miRNA expression with infertility. Method of study Observational, exploratory, preliminary study. A total of 287 multiple IVF failure infertile patients were recruited. Twenty fertile women, not IVF failure, were recruited as the control group. Swab samples were collected from the vagina and rectum. Microbial composition by NGS and miRNA expression by real‐time PCR of vaginal and rectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…15 Studies have explored the possible relationship between vaginal and rectal microbiome disbalances with infertility. 16 The 16S sequencing of vaginal, intestinal, urethral and oral secretions of the same participant showed significant differences in bacterial populations in these secretions.Studies have shown that the microbial composition in the upper genital tract, uterine cavity, fallopian tube, ovary, and other parts of the same participant is not completely identical. 17 Vaginal flora is related to female fertility, but its effects on the clinical pregnancy rate of AIH have not been reported.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…15 Studies have explored the possible relationship between vaginal and rectal microbiome disbalances with infertility. 16 The 16S sequencing of vaginal, intestinal, urethral and oral secretions of the same participant showed significant differences in bacterial populations in these secretions.Studies have shown that the microbial composition in the upper genital tract, uterine cavity, fallopian tube, ovary, and other parts of the same participant is not completely identical. 17 Vaginal flora is related to female fertility, but its effects on the clinical pregnancy rate of AIH have not been reported.…”
Section: Discussionmentioning
confidence: 93%
“…It is estimated that the total number of bacteria within the human microbiota is the same order of magnitude as the total number of cells that make up the human body 15 . Studies have explored the possible relationship between vaginal and rectal microbiome disbalances with infertility 16 . The 16S sequencing of vaginal, intestinal, urethral and oral secretions of the same participant showed significant differences in bacterial populations in these secretions.Studies have shown that the microbial composition in the upper genital tract, uterine cavity, fallopian tube, ovary, and other parts of the same participant is not completely identical 17 …”
Section: Discussionmentioning
confidence: 99%
“…Last, the gut microbiota is implicated in nutrient absorption, and de ciencies in trace elements and vitamins could have repercussions on fertility[66-68]. Concurrently, the gut microbiota's impact on body weight and metabolism should not be overlooked, as weight anomalies-be they obesity or underweight-are established to be detrimental to fertility [49,[69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…DNA and RNA were extracted simultaneously following the mirVana miRNA isolation kit for RNA protocol (Ambion, ThermoFisher Scientific, Waltham, MA). We chose this isolation kit as it is designed to efficiently isolate small RNAs (<200 nt) as well as total RNA which play a crucial role in regulating bacterial global gene expression and is routinely used for microbiome studies (Azpiroz et al 2021; Tong, Tang, and Wang 2023; Yost et al 2018). For RNA isolation, genomic DNA was removed using a Turbo DNA-free kit (Applied Biosystems, Ambion).…”
Section: Methodsmentioning
confidence: 99%